AUDITOR DYNAMICS ON AUDIT QUALITY - Pendi, Pendi; Lifaldi, Bahri; Uzliawati, Lia (Universitas Muhammadiyah Tangerang, 2023)
This study conducts a literature review on audit quality over the past few decades from various parts of the world. The main objective of this review is to evaluate the research contributions made in understanding audit quality issues and identify gaps in the literature that require further research. The reviewed studies in this research are grouped into seven different categories to provide a comprehensive framework of understanding. Through this review, existing knowledge on audit quality in the literature will be summarized, and research gaps will be identified. This provides a strong foundation for further research that can deepen our understanding of the factors influencing audit quality and their related consequences.